ANALISIS EKONOMI USAHA BUDIDAYA IKAN LELE SANGKURIANG (Clarias gariepinus) DI KOLAM TANAH DI KELURAHAN KARANG JOANG KECAMATAN BALIKPAPAN UTARA - Dimas Teguh Pribadi; Qoriah Saleha; Muhammad Syafril (2339-1324, 2022)
This study aimed to find out the profit and the feasibility of the Sangkuriang catfish farming business based on the following indicators: RCR, BEP (production, price, and sales), Payback Period, and ROI (Return On Investment). This study was conducted in Karang Joang urban village, North Balikpapan. The sampling method was the census method with a total respondent of 30 Sangkuriang catfish farmers. The result showed that the total profit was IDR 467,180,957 / production with an average amount of IDR 15,572,699 / respondent / production. The Sangkuriang catfish farming business, based on the RCR, BEP, Payback Period, and ROI, is feasible to be maintained.